Discovery of a nuclear haplotype potentially useful for the identification of medicinal rice Njavara (Oryza sativa L.) - Raj, R. Dinesh; Kumar, U. Suresh; Vinitha, M. R.; Patra, B. C.; Singh, O. N.; Thomas, George (Current Botany, 2024)
The present study report the development of an amplified fragment length polymorphism (AFLP)-derived sequence characterized amplified region (SCAR) marker for reliable identification of Njavara (Oryza sativa landrace Njavara), a rice landrace in India used extensively in health foods and Ayurveda treatments. The SCAR locus, named OsNSCAR131 after O. sativa landrace Njavara, is located on chromosome 3 between nucleotide positions 7793982 and 7794108, and yields a 131-bp allele in Njavara accessions and a 127-bp allele in other rice cultivars due to a 4-bp Insertion-Deletion (InDel) mutation at nucleotide position 7794026. We standardized the SCAR assay to be like those used for detecting microsatellite markers by using fluorescently (6-FAM) labeled primers and separating the alleles by capillary electrophoresis. As an alternative, we further adapted the method so as to allow allele detection by polyacrylamide gel electrophoresis (PAGE). A single rice grain can be tested for authentication by this PAGE assay. The SCAR marker developed here has great utility in authenticating Njavara grains in both the health food and pharmaceutical sectors.